2000
DOI: 10.1128/aem.66.2.836-838.2000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Catalase on Hydrogen Peroxide Penetration into Pseudomonas aeruginosa Biofilms

Abstract: The penetration of hydrogen peroxide into biofilms formed by wild-type and catalase-deficient Pseudomonas aeruginosa strains was measured using microelectrodes. A flowing stream of hydrogen peroxide (50 mM, 1 h) was unable to penetrate or kill wild-type biofilms but did penetrate and partially kill biofilms formed by an isogenic strain in which the katA gene was knocked out. Catalase protects aggregated bacteria by preventing full penetration of hydrogen peroxide into the biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 18 publications
10
107
1
2
Order By: Relevance
“…In addition, P. aeruginosa is an obligate aerobe that may be exposed to endogenous oxidative stress due to the metabolism of O 2 . Several mechanisms have been proposed in the literature for the defence of P. aeruginosa against oxidative intermediates (Mathee et al, 1999;Hassett et al, 1999;Stewart et al, 2000;Valente et al, 2000). An efficient way to scavenge reactive oxygen intermediates, which is unique to P. aeruginosa, is the formation of the exopolysaccharide alginate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, P. aeruginosa is an obligate aerobe that may be exposed to endogenous oxidative stress due to the metabolism of O 2 . Several mechanisms have been proposed in the literature for the defence of P. aeruginosa against oxidative intermediates (Mathee et al, 1999;Hassett et al, 1999;Stewart et al, 2000;Valente et al, 2000). An efficient way to scavenge reactive oxygen intermediates, which is unique to P. aeruginosa, is the formation of the exopolysaccharide alginate.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we could speculate that 2-CP penetration depth was about 400 mm in the treated biofilm during the experiments. Limited penetration of inhibitors into biofilms has been widely observed in previous investigations (de Beer et al, 1994;Stewart et al, 2001Stewart et al, , 2000Xu et al, 1996). In those articles, the concentration profiles of hydrogen peroxide or chlorine in biofilms were directly measured with microelectrodes and limited penetration of the biocides into the biofilms was demonstrated.…”
Section: Discussionmentioning
confidence: 89%
“…For example, microelectrode measurements of chlorine concentrations in biofilms directly showed that chlorine concentrations in the biofilms were typically only 20% or less of those in the bulk liquid (de Beer et al, 1994). Furthermore, microelectrode measurements of hydrogen peroxide penetration into biofilms revealed retarded penetration of the inhibitors (Stewart et al, 2000). Reduction of concentrations and hence the inhibitory effects of inhibitors in biofilm results in protecting bacteria in the deeper parts of the biofilm.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cerca de 99% de todas as bactérias em ambiente natural estão em biofilmes (DALTON; MARCH, 1998) que consistem de microrganismos aderidos a uma superfície auxiliados por substâncias poliméricas extracelulares (COSTERTON et al, 1994;DENYER;GORMAN;SUSSMAN, 1993;STEWART et al, 2000). Outra definição estabelece que o biofilme é a agregação de células microbianas, crescendo e se multiplicando em uma superfície, sendo essa agregação, promovida por substâncias poliméricas extracelulares produzidas pelos próprios microrganismos (FLINT; BREMER; BROOKS, 1997).…”
Section: Introductionunclassified